A Designed Durable Electrolyte for High‐Voltage Lithium‐Ion Batteries and Mechanism Analysis. Issue 35 (29th May 2020) - Zou, Yeguo; Shen, Yabin; Wu, Yingqiang; Xue, Hongjin; Guo, Yingjun; Liu, Gang; Wang, Limin; Ming, Jun
Abstract: Rechargeable lithium‐ion batteries (LIBs) dominate the energy market, from electronic devices to electric vehicles, but pursuing greater energy density remains challenging owing to the limited electrode capacity. Although increasing the cut‐off voltage of LIBs (>4.4 V vs. Li/Li + ) can enhance the energy density, the aggravated electrolyte decomposition always leads to a severe capacity fading and/or expiry of the battery. Herein, a new durable electrolyte is reported for high‐voltage LIBs. The designed electrolyte is composed of mixed linear alkyl carbonate solvent with certain cyclic carbonate additives, in which use of the ethylene carbonate (EC) co‐solvent was successfully avoided to suppress the electrolyte decomposition. As a result, an extremely high cycling stability, rate capability, and high‐temperature storage performance were demonstrated in the case of a graphite|LiNi0.6 Co0.2 Mn0.2 O2 (NCM622) battery at 4.45 V when this electrolyte was used. The good compatibility of the electrolyte with the graphite anode and the mitigated structural degradation of the NCM622 cathode are responsible for the high performance at high potentials above 4.4 V. This work presents a promising application of high‐voltage electrolytes for pursuing high energy LIBs and provides a straightforward guide to study the electrodes/electrolyte interface for higher stability. Abstract : A new durable electrolyte is designed for high‐voltage lithium‐ion batteries (i.e., graphite|NCM622) at 4.45 V for pursuing greater energy density. The good compatibility of the electrolyte with the graphite anode and mitigated structural degradation of the NCM cathode are confirmed to be responsible for the high performance (see figure).